Effects of L-Histidine and Sodium Acetate on β-Casein Expression in Nutrient-Restricted Bovine Mammary Epithelial Cells - Jungeun Kim (Animals, 2021)
Nutrient restriction is a challenging condition for the mammary glands of dairy cows. In this condition, supplementing amino acids and energy sources might be a good strategy to improve the concentration of one of the most important caseins in bovine milk. Therefore, the objective of this study was to investigate the effects of L-histidine (His) and sodium acetate (Ace) in a nutrient-restricted (NR) immortalized bovine mammary epithelial cell line (MAC-T cells). The treatments for the MAC-T cells are as follows: experiment (1) 0–5% diluted basal medium; experiment (2) supplementation of 0–9.6 mM of His or Ace in NR or normal conditions; experiment (3) supplementation of 0–9.6 mM of Ace plus 0.15 mM of His in NR or normal conditions. The 1% diluted medium showed no significant effect on the cell viability with the basal medium; thus, it was selected as the NR condition. The relative expression of β-casein was significantly increased in the NR condition with the inclusion of 0.15 mM His alone or with Ace compared to that in control. The supplementation of Ace increased the β-casein level under normal conditions. However, it did not change the expression of β-casein under the NR condition. The results suggest that His has the potential to increase the β-casein expression under the NR condition.